Motivasi Atlet Petanque Setelah Kejuaraan - Meysari, Ervina; Rasyono, Rasyono; Usra, Meirizal; Bayu, Wahyu Indra Bayu (Universitas Hamzanwadi, 2024)
This researcher wants to examine whether petanque athletes have the motivation to continue developing and increasing potential at the upcoming porprov XV in 2025. Because at the 2023 porprov event several districts and athletes who contributed participated, and the development of pentanque sports was not optimal. This study aims to examine whether there is motivation for petanque athletes after porprov XIV Year 2023. This study uses quantitative descriptive research with data collection methods. The population used was 88 petanque athletes. The sample in this study were 40 petanque athletes. Implementation and data collection using non-test technique methods in the form of questionnaires / surveys. The results of this study petanque athletes have high motivation, this refers to intrinsic motivation, namely encouragement from within athletes based on indicators of need, pleasure, and interest, which is 97.5%, while extrinsic motivation scores 87.5% which shows on a high category scale. with 39 athletes. Based on the data from the results of the analysis above, it can be concluded that the motivation of South Sumatra petanque athletes after porprov XIV Year 2023 is included in the high category, this refers to intrinsic motivation, namely encouragement from within athletes based on indicators of need, pleasure, and interest.